The Competence and Employability of Public Technical and Vocational Education and Training graduates in Khartoum State - Sudan - Mansour, Ahmed (Technium Social Sciences Journal, 2021)
This study's primary purpose was to examine public institutions' TVET graduate's competencies and employability in Khartoum State. To this end, the study used an explanatory sequential mixed method design. The researchers used primary and secondary sources of data. The primary sources were students, teachers, managers, and directors, whereas the secondary data were relevant policy documents. Eight hundred fifteen respondents from 12 TVET institutions were selected using stratified, simple random, and purposive sampling. Data collection instruments were questionnaires, a semi-structured interview guide, and Focus Group Discussions (FGD). Quantitative data were analyzed through descriptive (mean scores, standard deviation) and inferential statistics (one and two-sample t-test). The qualitative data were evaluated and interpreted with narration. The study found that graduates have fair competence and good employment opportunities. The study draws recommendations to policymakers and the TVET practitioners based on these results.